Perbedaan Pengetahuan, Sikap, dan Konsumsi Energi Sebelum dan Sesudah Penyuluhan Gizi Berbasis Media Online (Aplikasi VitaNutriHealth) pada Siswa dan Siswi Overweight di SMAN 1 Bululawang Malang - ISNAINI, NURUL; Riyadi, Bastianus Doddy; Hadisuyitno, Juin; Komalyna, I Nengah Tanu (NUTRITURE JOURNAL, 2025)
Background: Background: The prevalence of overweight and obesity among adolescents aged 16-18 years in East Java is 10.2% and 4.7% (SKI, 2023). Data from SSGI in 2022 shows that the prevalence of overweight in adolescents aged 15-18 years in East Java is 23%. This study was conducted on students as an effort to increase knowledge, change attitudes, and energy consumption, one of which is with nutritional interventions in the form of nutrition education. Objective: This study aims to determine the differences in knowledge, attitudes and energy consumption before and after online media-based nutrition education (VitaNutriHealth) in overweight students at SMAN 1 Bululawang Malang. Methods: This study used pre-experimental research with a quantitative approach with the design of One Group Pretest and Posttest Design conducted at SMAN 1 Bululawang Malang with purposive sampling technique and obtained a sample of 50 students. The intervention used was counseling using VitaNutriHealth media. Data collection instruments in the study used questionnaires and 24-hour recall forms. Data analysis used univariate, and bivariate using Paired Sample T-Test if the data is normally distributed and Wilcoxon Signed Test if the data is not normally distributed. Results and Conclusion: There is a significant difference between before and after nutrition counseling on knowledge, attitude and energy consumption of overweight students at SMAN 1 Bululawang Malang (p=0.000).